Analysis of the Influence of Product Attributes and Product Quality on Interest in Buying Pak Tani Npk Fertilizer 16.16.16 in Percut Sei Tuan Village - Rianto; Amril (LPPM STIE EKA PRASETYA, 2023)
This study aims to determine how big the influence of product quality and product attributes on interest in buying Pak Tani NPK 16.16.16 fertilizer in Percut Sei Tuan Village at PT. Fastgro Kimia Utama. The research methodology used is descriptive quantitative method, the unit of analysis in this study is PT. Fastgro Kimia Utama and the unit of observation are Farmers in Percut Sei Tuan Village. The population in this study were farmers in Percut Sei Tuan Village as many as 645 respondents. The technique for determining the number of samples used in this study was the slovin formula and amounted to 87 respondents. The research method used is data collection techniques through library research and field research which is carried out systematically based on the research objectives. The analytical method used to solve the problem and prove the hypothesis is descriptive analysis, regression analysis. This analysis includes validity and reliability, classical assumption test, multiple regression analysis, hypothesis testing through t and F tests, and coefficient of determination test (R2).